DETERMINATION OF GROWTH AND NUTRIENT ACCUMULATION IN BELLA VISTA ONION - Backes, Clarice (2017)
Knowledge of the nutrient uptake by crops at different stages of growth may provide the basis for rational application of fertilizers, which may lead to reduced production costs and improved use of fertilizers by plants. Based on this knowledge, we conducted this study to determine the biomass and nutrient accumulation curve of the onion cultivar Bella Vista in a system of transplanted seedlings. The experiment was carried out in Ituporanga–SC, Brazil, by using a randomized block design with three replicates. Eleven plant collections were carried out throughout the crop cycle. The variables evaluated included plant length; total dry biomass of leaves, bulbs, and roots; and concentrations of macro- and micronutrients. The maximum dry biomass accumulation in the shoots and bulbs at 140 days after transplanting (DAT) was 4.26 and 27.41 mg per plant, respectively, which contributed to 13% and 85% of the whole plant dry biomass at the end of the cycle, respectively. Potassium (K, 521.6 mg) was accumulated in the largest quantity per plant, followed by nitrogen (N, 465.7 mg), calcium (Ca, 253.3 mg), sulfur (S, 109.0 mg), magnesium (Mg, 86.9 mg), and phosphorus (P, 76.5 mg). The micronutrient accumulation was as follows: iron (Fe, 6,227.5 µg), boron (B, 902.3 µg), zinc (Zn, 573.7 µg), manganese (Mn, 573.7 µg), and copper (Cu, 241.4 µg).